Violinists, demandingness, and the impairment argument against abortion. (29th November 2019) - Crummett, Dustin
Abstract: The 'impairment argument' against abortion developed by Perry Hendricks aims to derive the wrongness of abortion from the wrongness of causing foetal alcohol syndrome (FAS). Hendricks endorses an 'impairment principle', which states that, if it is wrong to inflict an impairment of a certain degree on an organism, then, ceteris paribus, it is also wrong to inflict a more severe impairment on that organism. Causing FAS is wrong in virtue of the impairment it inflicts. But abortion inflicts an even more severe impairment (death), and so, ceteris paribus, is also wrong. Notably, Hendricks thinks that this argument does not require the claim that the foetus is a person. Here, I respond to Hendricks by arguing that the ceteris paribus clause of the impairment principle is not met in ordinary cases of pregnancy. Carrying an unwanted pregnancy to term is much more burdensome than is refraining from excessive drinking for nine months. This provides a pro tanto justification for obtaining an abortion that does not apply to causing FAS. If the foetus is not a person, it seems fairly clear to me that this justification is strong enough to render abortion permissible. Hendricks is therefore incorrect in claiming that the impairment argument can go without claims concerning foetal personhood. If the foetus is a person, then whether burdensomeness justifies abortion depends on certain questions relating to Thomson's famous violinist argument. I will not attempt to answer those. But anyone who is otherwise sympathetic to Thomson's argument should not be moved by the impairment argument.